IDENTIFICATION OF FLAVONOIDS FROM ACALYPHA INDICA L. (EUPHORBIACEAE) AS CASPASE-3 ACTIVATORS USING MOLECULAR DOCKING AND MOLECULAR DYNAMICS - FEBRINA, ELLIN; ASNAWI, AIYI; ABDULAH, RIZKY; LESTARI, KERI; SUPRATMAN, UNANG (International Journal of Applied Pharmaceutics, 2022)
Objective: The purpose of this study was to determine the structural-based molecular interactions between flavonoids contained in Acalypha indica L. and caspase-3 by molecular docking and molecular dynamics (MD) simulations. Methods: In a computer simulation, ten flavonoids contained in A. indica L. were evaluated for caspase-3 using the X-ray crystal structure of human caspase-3 (PDB ID 1NME). The AutoDock 4.2 software was used to study molecular docking, and MD simulations were done with GROMACS v2018. Results: The results of molecular docking identified the top four compounds, namely nicotiflorin, naringenin, hesperetin, and kaempferol, with docking scores of-6.81,-6.45,-6.33, and-6.10 kcal/mol, respectively. According to the MD simulation results, nicotiflorin was most effective in stabilizing the complex with caspase-3, with a total energy (ΔGbind, MM-PBSA) of-96.315 kcal/mol. Conclusion: This study showed that nicotiflorin was the flavonoid in A. indica L. that activated caspase-3 the best.